Analisis Pengendalian Kualitas Produk Reinforcement Suspension Member Menggunakan Metode Six Sigma - Dewin Purnama; Zulfikar Mutaqin (Politeknik Negeri Jakarta, 2023)
Customer satisfaction is the main requirement that must be provided by companies with products that meet the specified specifications, and quality is also a crucial factor in supporting customer satisfaction. The problem identified in this study is the occurrence of defects in reinforcement suspension member products that exceed the company's defect tolerance limit of 0.1%. The aim of this study is to analyze the causes of defects using the Six Sigma method with the DMAIC steps (Define, Measure, Analyze, Improve, and Control), and to propose improvements to address the number of defects that occur. Some of the tools used in this study are the fishbone diagram and the P control chart. The results of this study indicate that the factors causing the failures are the method and environment factors. Meanwhile, the data processing resulted in a DPMO of 2745.21 with a sigma level of 4.28 a process capability index (Cp) of 1.43, and an average defective product rate of 0.28% with a total of 392 defective pieces, while the company's defect tolerance limit is 0.1%. Therefore, the company needs to implement quality control by making improvements to the method and environment factors.